Fast frequency tracking - Prokopenko, I.G.; Omelchuk, I.P.; Chyrka, Yu.D.; Vovk, V.Yu. (Технология и конструирование в электронной аппаратуре, 2013)
A method of periodical signal frequency tracking by the frequency-locked loops is proposed. Increasing of frequency adjustment accuracy is achieved by using of a new fast frequency discriminator, based on estimates of an instantaneous frequency. Reasonability of an input signal pre-filtering in case of nonlinear distortions, harmonics interferences and strong noise is proved. Предлагается метод отслеживания частоты периодического сигнала. Повышение точности подстройки частоты достигается благодаря использованию нового быстрого частотного дискриминатора на базе оценок мгновенной частоты. Также доказывается целесообразность предварительной фильтрации входного сигнала в случае нелинейных искажений, гармонических помех и сильного шума. Пропонується метод відслідковування частоти періодичного сигналу. Підвищення точності підлаштування частоти досягається завдяки використанню нового швидкого частотного дискримінатора на основі оцінок миттєвої частоти. Також доводиться доцільність попередньої фільтрації вхідного сигналу у випадку нелінійних спотворень, гармонічних завад та сильного шуму.